The logic of opening Suning Stores - Yang, Bo, active 2019; Li, Dongxian; Dong, Hao, active 2019; Zhang, Xinrui (London : Renmin University, 2019)
This case analyzes the logic of opening Suning Stores from three perspectives: the two times of transformation of Suning, the logic of the community traffic, and the profit logic of the stores.
Originally Published InYang, B., Li, D., Dong, H., & Zhang, X. (2019). The Logic of Opening Suning Stores. Beijing, China: Renmin University Business School.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; New business enterprises -- Case studies; Stores, Retail -- Management -- Case studies; Entrepreneurship -- Case studies